Hope for animals and their world : how endangered species are being rescued from the brink - Goodall, Jane, 1934- (Grand Central Pub., 2009)
At a time when we are confronted with bad news about the environment nearly every day, renowned scientist Jane Goodall brings us inspiring news about the future of the animal kingdom. With the insatiable curiosity and conversational prose that have made her a bestselling author, Goodall--along with Cincinnati Zoo Director Thane Maynard--shares fascinating survival stories about the American crocodile, the California condor, the black-footed ferret and more--all formerly endangered species and species once on the verge of extinction whose populations are now being regenerated. Interweaving her own first-hand experiences with the research of premier scientists, Goodall illuminates the heroic efforts of dedicated environmentalists and the truly critical need to protect the habitats of these beloved species. At once a celebration of the animal kingdom and a passionate call to arms, this book presents an uplifting, hopeful message for the future of animal-human coexistence.